2016
DOI: 10.4103/0974-8490.171105
|View full text |Cite
|
Sign up to set email alerts
|

Crude extracts of marine-derived and soil fungi of the genus Neosartorya exhibit selective anticancer activity by inducing cell death in colon, breast and skin cancer cell lines

Abstract: Background:The crude ethyl acetate extracts of marine-derived fungi Neosartorya tsunodae KUFC 9213 (E1) and N. laciniosa KUFC 7896 (E2), and soil fungus N. fischeri KUFC 6344 (E3) were evaluated for their in vitro anticancer activities on a panel of seven human cancer cell lines.Materials and Methods:The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was performed, after 48 h treatments with different concentrations of extracts, to determine their concentration of the extract or Dox that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The obtained result may be associated with various types of cells tested and their other physiological functions. This is consistent with other reports, which demonstrate that different fungal extracts inhibit cell proliferation in a cell-speci c dependent manner at both short-and long-term (Ramos et al 2016;Wu et al 2014). Furthermore, fungi extracts have an antiproliferation effect on tumors through various intracellular signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…The obtained result may be associated with various types of cells tested and their other physiological functions. This is consistent with other reports, which demonstrate that different fungal extracts inhibit cell proliferation in a cell-speci c dependent manner at both short-and long-term (Ramos et al 2016;Wu et al 2014). Furthermore, fungi extracts have an antiproliferation effect on tumors through various intracellular signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…[ 31 32 ] We recently demonstrated that Dox can decrease cell viability in several cell models, and in some of them, induction of DNA damage and cell death occur. [ 16 ] However, one of the most resistant cell lines with higher IC 50 was A549 cell. [ 17 ] In this study, the results show that Dox at 0.54 μM decreased cell viability of A549 cells with induction of cell death being accomplished with nuclear condensation but without induction of strand breaks detected by comet assay.…”
Section: Discussionmentioning
confidence: 99%
“…Neosartorya tsunodae KUFC 9213 (E1) was isolated from a marine sponge, Aka coralliphaga , Neosartorya laciniosa KUFC 7896 (E2) was isolated from a diseased coral (ulcerative white spot in Porites lutea ), and Neosartorya fischeri KUFC 6344 (E3) was isolated from coastal forest soil, as described by Ramos et al . [ 16 ] Aspergillus similanensis KUFA 0013 (E4) was isolated from a marine sponge, Rhabdermia sp., Neosartorya paulistensis KUFC 7894 (E5) was isolated from a marine sponge, Chondrilla australiensis , and Talaromyces trachyspermum KUFC 0021 (E6) was isolated from a marine sponge, Clathria reianwardii , as reported by Ramos et al . [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine organisms are a source of many ingredients which have various useful roles in maintaining health. They can be applied in the fight against reactive oxygen species (ROS) [ 13 , 14 , 15 , 16 , 17 ] and in the treatment or prevention of infectious diseases [ 18 , 19 , 20 , 21 ], cancer diseases [ 22 , 23 , 24 , 25 , 26 ], diabetes [ 27 , 28 ], and obesity [ 29 , 30 , 31 ], as well as cardiovascular illnesses caused by hypertension [ 32 , 33 ]. Marine-derived compounds are used to produce drugs, pharmaceuticals, and supplements, as well as cosmetics.…”
Section: Introductionmentioning
confidence: 99%